QUANTIFICATION OF THE RISK OF CONTAMINATION OF COVID-19 IN THE FACE OF ESSENTIAL ACTIVITIES AND PROPOSAL FOR THE CAUSAL LINK AS AN OCCUPATIONAL DISEASE IN BRAZIL: QUANTIFICATION OF THE RISK OF CONTAMINATION OF COVID-19 IN THE FACE OF ESSENTIAL ACTIVITIES AND PROPOSAL FOR THE CAUSAL LINK AS AN OCCUPATIONAL DISEASE IN BRAZIL - Röhm, Daniel Gobato; Luciano, Erik Leonel; Rosa, Jorge Luiz; Tirelli, Marcelo Alexandre; Okano, Marcelo Tsuguio; Ribeiro, Rosinei Batista (Brazilian Journal of Production Engineering, 2020)
Introduction: The validation of the occupational disease occurs through research that proves the illness of the worker in the face of exposure to the causative agent. Objective: To apply a risk analysis tool as a device to verify the existence of a causal link between work and the illness caused by COVID-19. Methods: It adopted the quantification of a Contagion Risk Index (IRC) through the HRN (Hazard Rating Number) tool for professionals in essential areas, such as health, pharmacies, home office workers, among others. Results: Health professionals had a high CRI (7200), followed by attendants and workers from supermarkets (5700) and pharmacies (3840). As for home office work, the IRC was the lowest (1.188). Discussion/Conclusion: The degree of severity was adopted for risk analysis as a critical disease (DPH = 12), since what determines the causal link is contamination by COVID-19, which is linked to MP 927 that was used as vigorous of the discussion. It is concluded that the application of the risk analysis tool allowed to correlate the activity performed with the existence of an occupational disease caused by COVID-19 and as the case of underreporting of hospitalizations and deaths caused is underestimated, the CRI must be even higher.
Keywords: Covid-19; Pandemic; Occupational Disease; Causal Nexus; Risk Quantification.